An integrated marketing communications campaign for Foot Zone Makati - Dionisio, Ma. Franze N. (Animo Repository, 2017)
This integrated marketing communications campaign is put together as a final requirement for the graduate degree in Marketing Communications, first term, AY 2017. The IMC proposal to be presented is created to first, increase the brand awareness and promotion initiatives of Foot Zone Makati, and secondarily identify the marketing areas wherein Foot Zone Makati needs to improve on. The proposal will also take into account and consideration in tapping the market that is within its area of operations- Jupiter Street, Brgy. Bel-Air, in Makati, its neighboring executive village, nearby offices composed of small companies, BPOs, hotels, and restaurant businesses. Foot Zone Makati was opened only last April of 2016, the wellness shop is soon to enter its second year of operations. Needless to say, this wellness destination that specializes on Xiamen-style foot reflexology has yet to increase their brand promotion and awareness initiatives. Foot Zone Makati has only few known direct competitors in foot reflexology operating within the area. Foot Zone Makati does not just offer xiamen-style foot reflexology, it is positioned to be a premium wellness place that offers a variety of services as well, from the body massage- shiatsu and swedish foot reflexology and back massage as its main offering ear candling and head massage stone body massage ventosa therapy and even pedicure Chinese style. As a general background, the Wellness industry wherein Foot Zone Makati branding operates on a highly lucrative playing field. Globally, the Wellness industry is $ 3.72 Trillion, growing steadily at 10.6% from 2013- to 2015 industry according to the Global Wellness Institute. Wellness is defined as the active pursuit of activities, choices, and lifestyle that lead to a state of holistic health.